Effects of Chinese herbal mixture on performance, egg quality and blood biochemical parameters of laying hens. Issue 6 (14th April 2016) - Li, X. L.; He, W. L.; Wang, Z. B.; Xu, T. S.
Summary: The aim of the study was to evaluate the effect of Chinese herbal mixture (CHM) in laying hen diets on performance, egg quality and egg nutrition components, as well as selected blood biochemical parameters. A total of 270 Lohmann Brown laying hens, 24 week of age, were randomly distributed into three dietary treatments and fed for 6 week. The CHM was used at the levels of 0%, 0.5% and 1.0% in the diets of the control and two treatment groups respectively. Each dietary treatment was divided into five replicates, comprising of 18 hens each. Hens were housed in a 3‐tier battery system. Feed and water were provided ad libitum . Blood samples and eggs were collected at the end of the experiment. The results showed that dietary treatments did not affect egg weight, mortality, eggshell thickness, albumen height, Haugh units, eggshell‐breaking strength and egg‐shape index. Dietary supplementation of CHM significantly improved (p < 0.05) laying rate and the lowest feed conversion ratio were observed with 1.0% CHM supplementation diets. CHM supplementation decreased (p < 0.05) cracked‐egg rate, egg yolk cholesterol, blood serum levels of cholesterol, triglyceride, low‐density lipoprotein cholesterol (LDL‐C) and alanine aminotransferase (ALT) and increased blood serum levels of high‐density lipoprotein cholesterol (HDL‐C). No differences in serum total protein, serum albumen, serum glucose and aspartate amino transferase (AST) were observed in hens fed CHM. In conclusion, dietary supplementation with CHM improved egg production and egg quality and reduced serum cholesterol concentrations in laying hens. Dietary supplementation of 1.0% CHM in layer diets may be a feasible means of producing eggs with lower cholesterol and higher egg yolk phospholipid contents for health conscious consumers.